Regional Development Based on Regional Superior Potential as an Effort to Alleviate Poverty in Tual City - Mutmainnah, Mutmainnah; Renwarin, Francis D (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to identify leading sectors and analyze their impact on poverty reduction efforts in Tual City. This study uses quantitative methods using Location Quotient (LQ) analysis, Shift Share Analysis (SSA), Specialization Index (SI), and Klassen Typology, followed by multiple regression analysis to see the relationship between leading sectors and poverty rate. This study uses secondary data from the Central Bureau of Statistics (BPS) for the period 2019-2023. The results show that Tual City has six basic sectors: Agriculture, Forestry, and Fisheries (LQ 1.55-1.62); Construction; Wholesale and Retail Trade; Real Estate; Educational Services; and Health Services and Social Activities. The fisheries subsector shows a particular advantage, reflecting Tual's geographical advantage as an island city. Shift-share analysis shows that these sectors exhibit competitive advantage and positive growth patterns. This study concludes that the strategic development of these leading sectors, particularly the maritime-based economy, can contribute significantly to poverty alleviation in Tual City. The findings provide valuable insights for regional development planning and poverty alleviation strategies.